2021
DOI: 10.4018/ijvple.2021070105
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Flipped Learning Into an English Pre-Sessional Class at a Public University in the UAE

Abstract: This exploratory case study investigates the use of flipped learning in a second language classroom at a university in the United Arab Emirates (UAE). Flipped learning was researched as a possible teaching/learning strategy for this population. As this study was exploratory, a case study was chosen as the research method. Students in one class participated in the flipped learning approach for one semester. Results were triangulated through students' test scores, interviews with participants, and teacher reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They proceed at their own pace, and students are given the widest possible space to explore, express, and innovate independently and responsibly in terms of instilling the value of Pancasila values through stages, namely habituation, emotional awareness, and discipline. This is also the opinion of Eppard & Rochdi (2017) that children can learn at their own pace and according to their abilities. Each child has the opportunity to study independently and has a certain autonomy in terms of time management.…”
Section: Introductionmentioning
confidence: 83%
“…They proceed at their own pace, and students are given the widest possible space to explore, express, and innovate independently and responsibly in terms of instilling the value of Pancasila values through stages, namely habituation, emotional awareness, and discipline. This is also the opinion of Eppard & Rochdi (2017) that children can learn at their own pace and according to their abilities. Each child has the opportunity to study independently and has a certain autonomy in terms of time management.…”
Section: Introductionmentioning
confidence: 83%
“…The observable vector of resource features is calculated according to Eq. ( 8) and the expression is: (9) Where is the unobservable vector, is the factor loadings of journal resource integration features, and is the factor affecting . By calculating the journal resource characteristic observable vector, it is possible to understand the journal resources more deeply.…”
Section: Computing Observable Vectors For Journal Resource Characteri...mentioning
confidence: 99%
“…Eppard, J et al tested the flipped learning approach in a class for one semester, triangulated by exam scores of the students, interviews with participants, and instructor's reflections. The results indicated that flipped learning had positive outcomes in terms of increasing student self-efficacy, promoting leaner independent learning, and providing resources for concept introduction and review [9]. Wunderlich, J et al suggest that there is still a gap in how to select appropriate assemblies for different purposes and a need for guidance for practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Para Vygotsky, el lenguaje es un instrumento primordial para el desarrollo del pensamiento y posteriormente su evolución. Vygotsky propone que la base para comprender la conciencia humana, es el pensamiento y el lenguaje (Cripps et al, 2021;Eppard et al, 2021;Lázaro-Carrascosa et al, 2021).…”
Section: Introductionunclassified